Combinatorial optimization and applications : 12th International Conference, COCOA 2018, Atlanta, GA, USA, December 15-17, 2018, proceedings /: 12th International Conference, COCOA 2018, Atlanta, GA, USA, December 15-17, 2018, proceedings. ([2018]) - Unknown
No abstract available